2014
DOI: 10.1603/en13157
|View full text |Cite
|
Sign up to set email alerts
|

Ovipositional Preference and Larval Performance of the Banded Sunflower Moth (Lepidoptera: Tortricidae) and Its Larval Parasitoids on Resistant and Susceptible Lines of Sunflower (Asterales: Asteraceae)

Abstract: Banded sunflower moth, Cochylis hospes Walsingham, is one of the most destructive seed-feeding insect pests of sunflowers, causing significant economic yield losses in the northern Great Plains. In an attempt to understand host-plant resistance mechanisms for this pest, we field-tested, over several years, the effects of seven sunflower accessions, rated as resistant to C. hospes in previous screening trials, and a susceptible control (Par 1673-2), on the ovipositional preference and larval performance of C. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This class of diterpenoids occurs in many plant families, including Asteraceae, Annonaceae, Apiaceae, Celastraceae, Chrysobalanaceae, Erythroxylaceae, Euphorbiaceae, Fabaceae, Lamiaceae, Jungermanniaceae, Rhizophoraceae, Rutaceae, and Velloziaceae . Kaurenoic acid is an intermediate for many other diterpenoids, including the gibberellins, a class of plant hormones involved in development. , Many bioactivities have been attributed to kaurenoic acid, including antidiabetic properties, genotoxicity against some tumor cells, antifungal activity against Trichophyton rubrum , T. metagrophytes , and Epidermpphyton floccosum and as a phagostimulant . It has also shown activity against the botanical gray mold, Botrytis cinerea.…”
Section: Plant-derived Compounds With Antibacterial Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This class of diterpenoids occurs in many plant families, including Asteraceae, Annonaceae, Apiaceae, Celastraceae, Chrysobalanaceae, Erythroxylaceae, Euphorbiaceae, Fabaceae, Lamiaceae, Jungermanniaceae, Rhizophoraceae, Rutaceae, and Velloziaceae . Kaurenoic acid is an intermediate for many other diterpenoids, including the gibberellins, a class of plant hormones involved in development. , Many bioactivities have been attributed to kaurenoic acid, including antidiabetic properties, genotoxicity against some tumor cells, antifungal activity against Trichophyton rubrum , T. metagrophytes , and Epidermpphyton floccosum and as a phagostimulant . It has also shown activity against the botanical gray mold, Botrytis cinerea.…”
Section: Plant-derived Compounds With Antibacterial Propertiesmentioning
confidence: 99%
“…381,382 Many bioactivities have been attributed to kaurenoic acid, including antidiabetic properties, 383 genotoxicity against some tumor cells, 384−386 antifungal activity against Trichophyton rubrum, T. metagrophytes, and Epidermpphyton f loccosum 387 and as a phagostimulant. 388 It has also shown activity against the botanical gray mold, Botrytis cinerea. 389 A 2007 review of the kaurane diterpenoids discusses their bioactivities and synthesis in detail.…”
Section: Terpenoidsmentioning
confidence: 99%
“…Charlet et al (2009) evaluated resistance for H. annuus obtained from the United States National Plant Germplasm System (NPGS) using natural infestations; relative to the 25 interspecific crosses evaluated, several H. annuus entries from NPGS (abbreviated PI for "Plant Introduction" number) were found with equal or lower damage from banded sunflower moth feeding over five years. Additional research on some of these entries found evidence of decreased larval survival, but no chemical or physical cause of the antibiosis could be determined (Chirumamilla et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additional research on some of these entries found evidence of decreased larval survival, but no chemical or physical cause of the antibiosis could be determined (Chirumamilla et al . 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important of these head‐feeding pests in North America is the banded sunflower moth ( Cochylis hospes Walsingham [Lepidoptera: Tortricidae]) (Charlet & Busacca, 1986; Rogers, 1988; Knodel & Charlet, 2007). The banded sunflower moth is especially concerning as a pest due to its ability to overwinter in the northern Great Plains, which several other prominent insect pests of Helianthus are unable to do (Chirumamilla et al., 2014). As a result, the banded sunflower moth is one of the most consistent insect pests of Helianthus in North Dakota and South Dakota, which together account for over 75% of U.S. sunflower production (USDA National Agricultural Statistics Service, 2018).…”
Section: Introductionmentioning
confidence: 99%